Young adults’ struggles with their food environment – a case study using participatory video making in two agro-pastoralist communities in Turkana, Kenya - Jordan, Irmgard; Waswa, Lydiah M.; Nabuuma, Deborah; Termote, Celine; Keding, Gudrun B. (2025)
Food environments in the drylands of Turkana • Food environments is the space where consumers interact with the food system to make food decisions about what food to acquire, to prepare, to eat. • Turkana is characterized by a poorly built Food Environment, poor public transport system, poor road infrastructure, and high illiteracy levels.* • Limited information is available about the perceived food environment of young adults living in the drylands of Turkana.